Gas liquid chromatography in the rapid diagnosis of meningitis. Issue 12 (December 1977) - Ferguson, I R; Tearle, P V
Abstract : Gas liquid chromatography was employed to detect lactic acid in the cerebrospinal fluid of patients suspected of having bacterial meningitis. The technique was found to be both rapid and reliable. Differentiation between aseptic, purulent, and partially treated bacterial meningitis was readily achieved. The effectiveness of therapy in bacterial meningitis was indicated by a rapid fall in the concentration of lactic acid.